Sucrose but not arsenic induce hepatic steatosis which correlates with calpain-1 inhibition - Myrian Velasco; Rosa Isela Ortiz-Huidobro; Ana María Salazar; Marcia Hiriart; Patricia Ostrosky-Wegman; Pablo Pánico (PLoS ONE, 2025)
Exposure to arsenic or sugary drinks can increase the risk of developing metabolic dysfunction-associated steatotic liver disease (MASLD), although the mechanisms involved and its possible interactions remain unexplored. This work aimed to characterize the development of MASLD and their molecular mechanisms, induced in male Wistar rats consuming 20% sucrose (S), 50 ppm sodium arsenite (A), or both (A + S) through drinking water for 2 months. We found that rats consuming S developed liver steatosis and extensive fibrosis. Liver steatosis induced by S and A + S correlated with decreased calpain-1 protein abundance and calpain-dependent αII-spectrin proteolysis. We showed that calpain-1 inhibition in vitro induces lipid accumulation in hepatocytes probably by increasing PPARγ protein levels in the hepatic HepG2 cell line. Concordantly, PPARγ protein levels were increased in the livers of S-treated rats. A-treated rats did not develop steatosis, displayed decreased calpain-1 levels but its proteolytic activity remained intact. Treatment with A + S induced liver steatosis but displayed less fibrosis than S-treated rats. Although A + S reduced calpain-1 levels and activity, the levels of PPARγ were not induced in these rats. Our results suggest that liver steatosis induced by sucrose could be related with impaired calpain activity, which could promote PPARγ increase. However, some of these alterations induced by sucrose are attenuated by co-administering arsenic, suggesting that there are other calpain-dependent mechanisms involved in liver steatosis. The graphical abstract was generated using BioRender (License in S5 File).